Climate adaptive temperature correction for mitigating PV degradation in ASEAN climates - Arief Marwanto; Gunawan Gunawan; Imam Much Ibnu Subroto; Mochammad Facta; Munawar Agus Riyadi; Tole Sutikno (SINERGI, 2026)
The emphasis on the ASEAN area is appropriate due to its unique tropical environment, characterized by elevated temperatures, high humidity, and little seasonal fluctuations. These features affect PV operating temperatures and degradation patterns in ways that current temperature correction models designed for other tropical areas inadequately address. In tropical regions, photovoltaic modules frequently operate at temperatures exceeding 35 °C, which is above the Standard Test Conditions of 25 °C.  The conventional linear temperature correction (γ ≈ –0.45%/°C) fails to account for nonlinear thermal effects, leading to an underestimation of losses, battery under sizing, and a reduction in system lifespan.  This study presents a nonlinear temperature correction model that incorporates a severity factor (δ) for cell temperatures exceeding 35 °C.  The model utilizes two regimes: linear (≤35 °C) and quadratic (>35 °C) to account for nonlinear degradation.  Simulations conducted at 45 °C and 1000 W/m² for a 100 WP panel indicate that the proposed model predicts an output of 90.575 W, compared to 81.9 W from the conventional model, resulting in an approximate 9.5% improvement in accuracy.  This method addresses a significant gap by incorporating high-temperature nonlinearities, thereby enhancing the reliability of photovoltaic output predictions and improving battery sizing in tropical climates.  This contribution enhances the reliability of photovoltaic systems and extends battery lifespan for applications in Indonesia and ASEAN.